Palladium and copper catalyzed Sonogashira decarboxylative coupling of aryl iodides and alkynyl carboxylic acids. Issue 30 (27th July 2016) - Maaliki, Carine; Chevalier, Yoan; Thiery, Emilie; Thibonnet, Jérôme
Graphical abstract: Highlights: The use of microwave conditions that optimize the reaction time. Transferring small alkyne patterns on aryl bromide and iodide. A methodology using conventional reagents and easy to implement. Abstract: A mild procedure of palladium and copper catalyzed decarboxylative cross-coupling reaction of aryl halides and alkynyl carboxylic acids has been developed. Low molecular weight acids, to introduce small building blocks, were specifically used. This methodology is easy to implement and uses common reactants and catalysts.